Rachunkowość zarządcza wobec kontroli przedsięwzięć - Klinowski, Marcin (Management Accounting Towards Projects Control, 2006)
Management by projects is more and more often applied by companies nowadays. The proper control is essential to execute every project. Its role becomes more important when the project is complex. The foregoing paper presents Earned Value Method as a management accounting instrument which makes possible to control projects even when they are very complex.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (4); 2006; nr 1119, s. 44-50